Policy Studies of Educational Finance for Teacher Education in Indonesia - SUMARTO, SUMARTO; FATTAH, Nanang; SURYANA, SURYANA; ABUBAKA, ABUBAKA (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).31, 2019)
This paper is about policies on educational finance for teacher education in Indonesia. The author looks at how financing education has been conducted in Indonesia more so for the higher education sector. It is believed that the quality of education will highly depend on the amount of funds allocated. The paper explores how this has been done in the last few years within Indonesia.